Onorati gentiluomini e duellanti impavidi. La cultura nobiliare e gli ideali cavallereschi nella trattatistica sul duello del secondo Cinquecento - Fiazza, Giovanni (Consonanze, 2023)
From the middle of the 16th century, the practice of duelling, by then closely linked to the principle of honour and the defence of its integrity, became the subject of a large number of treatises addressed to a large audience of gentlemen, eager to know the most honourable ways to come to terms with the disputes that often involved them. Treatises on the duel, whose diffusion was favoured by the use of the vernacular and the intense publishing activity of the time, gave rise to a discipline, the science of chivalry, which played a decisive role in the diffusion of the myth of chivalry and in the definition of a common noble ethos. Through an indepth study, in Onorati gentiluomini e duellanti impavidi Giovanni Fiazza highlights the foundations of a way of understanding the division between the classes and social relations that would come to an end only two centuries later, with the end of the Old Regime.